Surveillance as social sorting : privacy, risk, and digital discrimination - Lyon, David, 1948- (Routledge, 2003)
Surveillance happens to all of us, everyday, as we walk beneath street cameras, swipe cards, surf the net. Agencies are using increasingly sophisticated computer systems - especially searchable databases - to keep tabs on us at home, work and play. Once the word surveillance was reserved for police activities and intelligence gathering, now it is an unavoidable feature of everyday life. Surveillance as Social Sorting proposes that surveillance is not simply a contemporary threat to individual freedom, but that, more insidiously, it is a powerful means of creating and reinforcin.